A convenient numbering-up strategy for the scale-up of gas–liquid photoredox catalysis in flow. Issue 1 (4th November 2015) - Su, Yuanhai; Kuijpers, Koen; Hessel, Volker; Noël, Timothy
Abstract : An operationally simple numbering-up strategy for the scale-up of gas–liquid photocatalytic reactions was developed, which provides an excellent flow distribution (SD w < 10%). Abstract : Visible-light photocatalysis is a mild activation method for small molecules and enables a wide variety of transformations relevant for organic synthetic chemistry. However, one of the limitations of photocatalysis and photochemistry in general is the limited scalability due to the absorption of light (Lambert–Beer law). Here, we report the development of a convenient numbering-up strategy for the scale-up of gas–liquid photocatalytic reactions in which the gas is consumed. Only commercially available constituents were used and the system can be rapidly assembled by any practitioner of flow chemistry. The modular design allows us to systematically scale the photochemistry within 2 n parallel reactors (herein, n = 0, 1, 2, 3). The flow distribution in the absence of reactions was excellent, showing a standard deviation less than 5%. Next, we used the numbered-up photomicroreactor assembly to enable the scale-up of the photocatalytic aerobic oxidation of thiols to disulfides. The flow distribution was again very good with a standard deviation lower than 10%. The yield of the target disulfide in the numbered-up assemblies was comparable to the results obtained in a single device demonstrating the feasibility of our approach.